Early Cretaceous angiosperms and beetle evolution - Wang, Bo; Zhang, Haichun; Jarzembowski, Edmund (Frontiers in Plant Science, 2013)
The Coleoptera (beetles) constitute almost one-fourth of all known life-forms on earth. They are also among the most important pollinators of flowering plants, especially basal angiosperms. Beetle fossils are abundant, almost spanning the entire Early Cretaceous, and thus provide important clues to explore the co-evolutionary processes between beetles and angiosperms. We review the fossil record of some Early Cretaceous polyphagan beetles including Tenebrionoidea, Scarabaeoidea, Curculionoidea, and Chrysomeloidea. Both the fossil record and molecular analyses reveal that these four groups had already diversified during or before the Early Cretaceous, clearly before the initial rise of angiosperms to widespread floristic dominance. These four beetle groups are important pollinators of basal angiosperms today, suggesting that their ecological association with angiosperms probably formed as early as in the Early Cretaceous. With the description of additional well-preserved fossils and improvements in phylogenetic analyses, our knowledge of Mesozoic beetle-angiosperm mutualisms will greatly increase during the near future.